Perilaku Seksual Remaja SMA Negeri Se-Kota Pekanbaru Tahun 2012 - Hastuti Marlina; Buchari Lapau; Ezalina . (STIKes Hang Tuah Pekanbaru, 2013)
Adolescent sexual behaviors are all types of behavior motivated by sexual desire to the opposite sex as well as to same sex. Types of adolescent sexual behavior is ranging from less to the most intimate level (sexual intercourse). 15-24 years old adolescent who had experienced sexual intercourse by 66.55% globally, 2.2% in Malaysia, 45% in Riau province and 44.23% in Pekanbaru. The study was conducted to determine the factors associated with sexual behavior of SMA adolescent in Pekanbaru in 2012. This study was a quantitative research by cross sectional design. The samples are 1000 SMA adolescents of Pekanbaru. The sampling procedure was by systematic random sampling, data collection was using questionnaires and data analysis was carried out by univariate, bivariate with chi-square test and multivariate logistic regression to test double. The results shows the proportion of adolescents who engaged in risky sexual behavior by 280 peoples (28%). Variables related to sexual behavior of adolescents were parental supervision (OR: 115, 95% CI: 13.24 to 999, 72), myths about sex (OR: 12, 95% CI :2,61-57, 32), lifestyle (OR: 8, 95% CI: 1.35 to 47.46) and gender (OR: 0.2, 95% CI : 0.06 to 0.61), variable not associated with adolescent sexual behavior was recidency during school year and other variables counfounding with the dependent variable and independent. It is expected a cooperation between health institution and Department of Education in terms of providing good education to parents, teachers and adolescents themselves about the risks of sexual behavior, sexually transmitted diseases, myths about sex and so on